3D localized lactate detection in muscle tissue using double‐quantum filtered 1H MRS with adiabatic refocusing pulses at 7 T. Issue 3 (31st October 2021) - Niess, Fabian; Roat, Sigrun; Bogner, Wolfgang; Krššák, Martin; Kemp, Graham J.; Schmid, Albrecht I.; Trattnig, Siegfried; Moser, Ewald; Zaitsev, Maxim; Meyerspeer, Martin
Abstract : Purpose: Lactate is a key metabolite in skeletal muscle and whole‐body physiology. Its MR visibility in muscle is affected by overlapping lipid signals and fiber orientation. Double‐quantum filtered (DQF) 1 H MRS selectively detects lactate at 1.3 ppm, but at ultra‐high field the efficiency of slice‐selective 3D‐localization with conventional RF pulses is limited by bandwidth. This novel 3D‐localized 1 H DQF MRS sequence uses adiabatic refocusing pulses to unambiguously detect lactate in skeletal muscle at 7 T. Methods: Lactate double‐quantum coherences were 3D‐localized using slice‐selective Shinnar–Le Roux optimized excitation and adiabatic refocusing pulses (similar to semi‐LASER). DQF MR spectra were acquired at 7 T from lactate phantoms, meat specimens with injected lactate (exploring multiple TEs and fiber orientations), and human gastrocnemius in vivo during and after exercise (without cuff ischemia). Results: Lactate was readily detected, achieving the full potential of 50% signal with a DQF, in solution. The effects of fiber orientation and TE on the lactate doublet (peak splitting, amplitude, and phase) were in good agreement with theory and literature. Exercise‐induced lactate accumulation was detected with 30 s time resolution. Conclusion: This novel 3D‐localized 1 H DQF MRS sequence can dynamically detect glycolytically generated lactate in muscle during exercise and recovery at 7 T.